Assessment of Heart Rate Variability Thresholds from Incremental Treadmill Tests in Five Cross-Country Skiing Techniques - Mendia-Iztueta, Ibai (PLoS One, 2016)
The assessment of heart rate variability (HRV) thresholds (HRVTs) as an alternative of Ventilatory thresholds (VTs) is a relatively new approach with increasing popularity which has not been conducted in cross-country (XC) skiing yet. The main purpose of the present study was to assess HRVTs in the five main XC skiing-related techniques, double poling (DP), diagonal striding (DS), Nordic walking (NW), V1 skating (V1), and V2 skating (V2).Ten competitive skiers completed these incremental treadmill tests until exhaustion with a minimum of one to two recovery days in between each test. Ventilatory gases, HRV and poling frequencies were measured. The first HRV threshold (HRVT(1)) was assessed using two time-domain analysis methods, and the second HRV threshold (HRVT(2)) was assessed using two non-time varying frequency-domain analysis methods. HRVT(1) was assessed by plotting the mean successive difference (MSD) and standard deviation (SD) of normalized R-R intervals to workload. HRVT(1) was assessed by plotting high frequency power (HFP) and the HFP relative to respiratory sinus arrhythmia (HFP(RSA)) with workload. HRVTs were named after their methods (HRVT(1-SD); HRVT(1-MSD); HRVT(2-HFP); HRVT(2-HFP-RSA)). The results showed that the only cases where the proposed HRVTs were good assessors of VTs were the HRVT(1-SD) of the DS test, the HRVT(1-MSD) of the DS and V2 tests, and the HRVT(2-HFP-RSA) of the NW test. The lack of a wider success of the assessment of HRVTs was reasoned to be mostly due to the high entrainment between the breathing and poling frequencies. As secondary finding, a novel Cardiolocomotor coupling mode was observed in the NW test. This new Cardiolocoomtor coupling mode corresponded to the whole bilateral poling cycle instead of corresponding to each poling action as it was reported to the date by the existing literature.